DairyWater: striving for sustainability within the dairy processing industry in the Republic of Ireland. Issue 3 (8th August 2018) - Finnegan, William; Clifford, Eoghan; Goggins, Jamie; O'Leary, Niall; Dobson, Alan; Rowan, Neil; Xiao, Liwen; Miao, Song; Fitzhenry, Kelly; Leonard, Peter; Tarpey, Emma; Gil-Pulido, Beatriz; et al.
Abstract : This Review describes the objectives and methodology of the DairyWater project as it aims to aid the Irish dairy processing industry in achieving sustainability as it expands. With the abolition of European milk quotas in March 2015, the Republic of Ireland saw a surge in milk production. The DairyWater project was established in anticipation of this expansion of the Irish dairy sector in order to develop innovative solutions for the efficient management of water consumption, wastewater treatment and the resulting energy use within the country's dairy processing industry. Therefore, the project can be divided into three main thematic areas: dairy wastewater treatment technologies and microbial analysis, water re-use and rainwater harvesting and environmental assessment. In order to ensure the project remains as relevant as possible to the industry, a project advisory board containing key industry stakeholders has been established. To date, a number of large scale studies, using data obtained directly from the Irish dairy industry, have been performed. Additionally, pilot-scale wastewater treatment (intermittently aerated sequencing batch reactor) and tertiary treatment (flow-through pulsed ultraviolet system) technologies have been demonstrated within the project. Further details on selected aspects of the project are discussed in greater detail in the subsequent cluster of research communications.